2017
DOI: 10.11604/pamj.2017.28.176.10261
|View full text |Cite
|
Sign up to set email alerts
|

Intérêt de l’enclouage centromédullaire dans les fractures du quart distal de la jambe: à propos de 30 cas

Abstract: Les fractures du quart distal de la jambe, sont des fractures dont le trait est situé au niveau du quart inférieur du tibia. Elles sont réputées graves et posent à la fois des problèmes de consolidation, de contention et de stabilité. Nous présentons l'expérience du service de traumatologie orthopédie de l'Hôpital militaire Avicenne de Marrakech, concernant 30 fractures fermées du quart inférieur de la jambe, sur une période de 10 ans (de Janvier 2001 à Décembre 2010) ayant reçu un enclouage centromédullaire. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Intramedullary nailing is the treatment of choice for shaft fractures of long limb bones. Locking has extended its indications to complex shaft fractures and metaphyseal-diaphyseal fractures [11]. In our study, we observed a case of residual valgus on locked nail in a patient operated for distal leg mal-union.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Intramedullary nailing is the treatment of choice for shaft fractures of long limb bones. Locking has extended its indications to complex shaft fractures and metaphyseal-diaphyseal fractures [11]. In our study, we observed a case of residual valgus on locked nail in a patient operated for distal leg mal-union.…”
Section: Discussionmentioning
confidence: 59%
“…Omar Margal et al [11], the distal locking must have at least 2 screws to promote the stability of the assembly. Thoreux et al [6] in his study reports that valgus leg shaft mal-union are often seen when the fracture sits at the distal quarter of the leg.…”
Section: Discussionmentioning
confidence: 99%